Is sulfoxaflor a safe alternative to neonicotinoids for Apis mellifera? A systematic review - de Souza, Guilherme Duarte Figueiredo [UNESP]; de Castro Lippi, Isabella Cristina [UNESP]; do Rosário Corrêa Moreira, Iloran [UNESP]; da Silva, Suelen Matos [UNESP]; da Luz Scheffer, Jaine [UNESP]; Astolfi, Aline [UNESP]; Arruda, Renato Agostinho [UNESP]; de Oliveira Orsi, Ricardo [UNESP] (Springer Nature, 2025)
Despite their importance to the ecosystem, global food production, and the beekeeping industry, honey bees are systematically threatened by multiple factors. Industrial agriculture plays an important role in such a process challenging both managed and wild bees. While the impacts of various insecticide classes on bees are well-documented, neonicotinoids are closely associated with colony losses, prompting their ban in several countries. Sulfoxaflor, a sulfoximine-based insecticide, has been proposed as a replacement for neonicotinoids like imidacloprid, targeting nicotinic acetylcholine receptors (nAChRs) through a distinct binding mechanism and allegedly posing lower risks to birds, mammals, and humans. This review systematically assesses sulfoxaflor’s effects on Apis mellifera, utilizing data from PubMed, Web of Science, Jstor, Scopus, Google Scholar, CORE, and the Directory of Open Access Journals (DOAJ) for studies published between 2019 and 2024. Nineteen studies were selected, excluding research on non-Apis bees or combined formulations. Findings revealed diverse sublethal impacts on honey bees, including metabolic, morphological, behavioral, and gene expression alterations. Even though sulfoxaflor is less toxic than neonicotinoids, it cannot be deemed a safe alternative for honey bees, especially once that many effects have been reported in both classes of pesticides.